A comparative study of cannibalism and predation in seven species of flour beetle - Alabi, Taofic; Michaud, J. P.; Amaud, Ludovic; Haubruge, Eric (My University, 2008)
1. The present study quantified egg and pupal cannibalism, and interspecific predation on eggs and pupae, by larvae and adults of seven species of flour beetle ( Tribolium spp.) under laboratory conditions: T. anaphe , T. brevicornis , T. castaneum , T. confusum , T. destructor , T. freemani , and T. madens. 2. Variation among species in cannibalism and predation propensities did not reflect taxonomic affinities within the genus, indicating that these behaviours were shaped by ecology at species level. 3. Within species, larvae and adults displayed different propensities for cannibalism and predation, leading to the conclusion that these behaviours evolve independently in the two life stages. 4. All species behaved as intraguild predators to some degree, especially in the adult stage. 5. Three general patterns of cannibalism and predation were described by principal component mapping and cluster analysis. 6. The first group comprised three cosmopolitan pest species that were more voracious as adults than as larvae: T. castaneum , T. confusum , and T. destructor . It is proposed that stored product environments select for high adult voracity because the costs associated with emigration from such rare, but resource-rich, habitats intensifies interference competition among adults. 7. The second group consisted of species that inhabit natural environments and that were more voracious as larvae: T. anaphe , T. freemani , and T. madens . Habitats for these species are probably numerous, but generally poor in quality, a situation that intensifies larval competition, while favouring earlier adult emigration. 8. The largest species, T. brevicornis , demonstrated inconsistent voracity between life stages and was the only species with chemically defended pupae. 9. It is proposed that consumption of eggs provides primarily nutritional benefits, whereas consumption of pupae has a more important role in interference competition.
Citation: Alabi, T., Michaud, J.P., Arnaud, L., & Haubruge, E. (2008). A comparative study of cannibalism and predation in seven species of flour beetle. Retrieved fromhttp://krex.ksu.edu
Keywords: Adults; Cannibalism; Eggs; Intraguild predation; Larvae; Pupae; Tenebrionidae; Tribolium